An Overview on Cardiovascular Protective Effects of Catechins - Shaterzadeh-Yazdi, Hanieh; Farkhondeh, Tahereh; Samarghandian, Saeed (Cardiovascular & Haematological Disorders - Drug Targets, 2017)
Background: The impact of diet strategies to manage cardiovascular disease has been focused in recent years. The food ingredients, such as flavonoids, are known as cardioprotective agents; however, it is not fully understood how these compounds are effective against cardiovascular problems. Catechins are polyphenolic compounds exhibiting several biological activities in the human body, potentially in the treatment of cardiovascular disease. The present study indicates that catechins may be effective against cardiovascular problems through modulating blood lipid metabolism, protecting vascular endothelial, and decreasing blood pressure. Conclusion: The current review has evaluated various studies on the role of catechins in the prevention and treatment of cardiovascular disorders by focusing on oxidative stress and inflammatory responses.
Keywords: antioxidancts